Problems of Perception and Comprehension of Literary Text by Students-Bilinguals - N. L. Kolchikova (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The study deals with the problem of the perception of a foreign culture text by students-bilinguals. Special attention is paid to the fact that when teaching Khakass students the Russian literature, it is necessary to take into account their bilingualism - the ability to use two language systems for communication, as well as the features of national psychology. It is noted that Khakass students communicate in their native language mainly in ethnic group (family, relatives, friends, etc.), all the rest of their communication is in a non-native language. It is emphasized that in this regard, the study of Russian literature should take into account the specificity of the perception of the literary text by students-bilinguals. It is proved that such a student can become a qualified reader of the works of Russian literature on the condition of teaching reading skills and comprehension of the foreign culture text. The novelty of the study is determined by the fact that the authors rely on data of the associative experiment conducted on the basis of ethno-cultural vocabulary on the works of Russian classical literature. It is concluded that the differences in perception of Khakass students in comparison with Russian students appear not only to the reactions on the Russian stimulus word, but in the main directions of the association. The article proposes a classification of reading skills, taking into account the peculiarities of perception of the literary text by students-bilinguals.